Java fundamentals (Manning Publications, 2022)
Java Fundamentals is a comprehensive video course introducing the core elements of Java programming. In over 14 hours of professionally produced video, along with ample opportunities to try out what you’re learning, you’ll master the essentials in a friendly, easy-to-understand way. You’ll not only dig into the syntax and structure of the Java language, but also build up good habits and practices as you work with the many hands-on examples. As you progress from section to section, you’ll incrementally build a fully functioning application by adding and refining features.